Effect of Polysaccharide Extracted From Gynostemma Pentaphyllum on the Body Weight and Gut Microbiota of Mice - Li, Shiwei; Wang, Yingna; Dun, Weipeng; Han, Wanqing; Ning, Tao; Sun, Qi; Wang, Zichao (Frontiers in Nutrition, 2022)
Researchers have investigated the role of polysaccharides in disease treatment via gut microbiota regulation but ignore their function in disease prevention and physique enhancement. In this work, a Gynostemma pentaphyllum polysaccharide (GPP) was tested by methyl thiazolyl tetrazolium (MTT) assay and proved to be safe to Caco-2 cells. Animal experiments showed that the administration of GPP for 3 weeks decreased the body weight gain of mice from 15.4 ± 1.7 g to 12.2 ± 1.8 g in a concentration-dependent manner. Analysis of short-chain fatty acids (SCFAs) indicated that GPP increased the levels of acetate, propionate, butyrate, and total SCFAs in the cecum contents of normal mice. Furthermore, GPP improved the species richness and abundance in the gut microbiota but reduced the Firmicutes/Bacteroidetes ratio from 0.8021 to 0.3873. This work provides a basis for incorporating GPP into diet to prevent or mitigate the occurrence of obesity via gut microbiota regulation.